2005
DOI: 10.1191/1358863x05vm635oa
|View full text |Cite
|
Sign up to set email alerts
|

The association between smoking and the prevalence of intermittent claudication

Abstract: The objective of this study was to investigate the association between smoking and the prevalence of intermittent claudication (IC). Between 1995 and 1997, all residents aged 20 years or older in Nord-Trøndelag County, Norway, were invited to take part in the Nord-Trøndelag Health Study (Helseundersøkelsen i Nord-Trøndelag: HUNT 2). A total of 19 748 participants aged 40-69 years attended. Responses to 12 questions on IC (including a Norwegian translation of the Edinburgh Claudication Questionnaire) had been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72. One study (1.8%) used both the ABI and a claudication questionnaire, and examined symptomatic and asymptomatic PAD separately 27…”
Section: Resultsmentioning
confidence: 99%
“…Forty-three (78.2%) were cross-sectional studies,22–26 28–31 33 34 36 40–45 47–50 52–55 57–71 74 75 10 (18.2%) were cohort studies21 27 32 38 39 46 51 56 72 73 and 2 (3.6%) were case-control studies 35 37. Forty-seven (84.5%) studies defined PAD using the ABI,21–26 29–34 36–38 40–49 52–55 57–71 73–75 and 7 (12.7%) based on symptoms of intermittent claudication, using either the Edinburgh, WHO/Rose or San Diego claudication questionnaires 28 35 39 50 51 56 72. One study (1.8%) used both the ABI and a claudication questionnaire, and examined symptomatic and asymptomatic PAD separately 27…”
Section: Resultsmentioning
confidence: 99%
“…Those who smoke tend to have worse clinical peripheral artery disease and associated intermittent claudication. One reason for this is that there is poor collateral vessel formation, leading to symptoms which are generally worse than those in patients who do not smoke [48,49]. Studies have also shown that patients who smoke have a blunted effect of antihypertensive medication on arterial vasodilatation [50].…”
Section: Discussionmentioning
confidence: 97%
“…19,20 Further, diabetes was substantially more strongly associated with IC compared to similar associations with smoking and blood lipids in the same population during the same time period. 7,21 Type 2 DM is the most common form of diabetes. In younger patients, however, there will be a relatively larger proportion with type 1 DM.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 There is an increased incidence and prevalence of DM in almost all age groups in the western world; however, especially in the young. 6,7 Further, the duration of DM is associated with the development of PAD. 8,9 It is therefore likely that the number of patients in the population who suffer from vascular diseases will increase due to a higher prevalence of DM in the general population.…”
Section: Introductionmentioning
confidence: 99%